Lumbar puncture refusal in febrile convulsion - Ling, S.G.; Boey, Christopher Chiong Meng (Stamford Publishing Pte Ltd / Singapore Medical Association, 2000)
A descriptive study was carried out on patients admitted for febrile convulsion over a two-year period to determine rate of lumbar puncture (LP) refusal, factors associated with LP refusal and outcome of such patients. From 77 patients indicated and requested for LP, 19 (25) patients refused the procedure. Refusal of LP was significantly more common among the Malay ethnic group (p=0.01) but not significantly associated with age, gender or whether the patient was admitted for a first or recurrent febrile convulsion. Half of the patients who refused LP had to be started empirically on antibiotics for meningitis. Patients who refused LP were also 8.5 times more likely to discharge themselves âat own riskâ (AOR), compared to other patients with febrile convulsion (p=0.004). In conclusion, LP refusal is a common problem in the local setting and is a hindrance to the proper management of patients with fever and seizure. Appropriate measures must be carried out to educate the public, particularly those from the Malay ethnic group on the safety and usefulness of the procedure. Reasons for patients discharging AOR following LP refusal also need to be addressed and problems rectified.